Molecular and Cellular Biology of Neuroprotection in the CNS - Alzheimer, Christian (Springer US, 2002)
Given the very limited capacity of regeneration in the brain, protecting neurons that are on the brink of death is a major challenge for basic and clinical neuroscience, with implications for a broad spectrum of acute and chronic neurological and psychiatric diseases. This book brings together leading experts from neurobiology, neurophysiology, neuropharmacology, neuroimmunology and clinical neuroscience to highlight the most recent milestones in this rapidly evolving field. The book will serve as a reference for both basic neuroscientists and clinicians interested in an authoritative update on the molecular and cellular biology of neuroprotection and its promises for new therapeutic strategies
Keywords: Neurosciences; Pharmacology/Toxicology; Toxicology; Cytoprotektion; Nervenzelle; Zentralnervensystem; Aufsatzsammlung